Protocol for the End-of-Life Social Action Study (ELSA): a randomised wait-list controlled trial and embedded qualitative case study evaluation assessing the causal impact of social action befriending services on end of life experience. Issue 1 (December 2016) - Walshe, Catherine; Algorta, Guillermo; Dodd, Steven; Hill, Matthew; Ockenden, Nick; Payne, Sheila; Preston, Nancy
Abstract Background Compassionate support at the end of life should not be the responsibility of health and social care professionals alone and requires a response from the wider community. Volunteers, as community members, are a critical part of many end-of-life care services. The impact of their services on important outcomes such as quality of life is currently poorly understood. The purpose of this study is to evaluate a series of social action initiatives which use volunteers to deliver befriending services to people anticipated to be in their last year of life. The aim is to determine if receiving care from a social action volunteer befriending service plus usual care significantly improves quality of life in the last year of life. Methods/design The research questions will be addressed through a wait-list randomised controlled trial (WLRCT) and qualitative case study evaluation across 12 sites in England. Participants will be randomly allocated to either receive the social action volunteer befriending service straight away or receive the intervention after a four week wait (wait-list arm). The impact of the intervention on end-of-life experience (quality of life as primary outcome, loneliness, social support) will be measured. Repeated assessments will be carried out at baseline and weeks 4 and 8 for the intervention arm and weeks 4, 8 and 12 for the wait-list arm. For selected sites case study evaluation will include interviews, observation and documentary analysis to understand the mechanisms underpinning any found impact. Discussion This study will address the need to both provide services which use social action models to support end-of-life care in community settings, and to robustly evaluate these models to determine if they influence the experience of end-of-life care. Such services could work to reduce isolation, help meet emotional needs and maintain a sense of connectedness to the community. ISRCTN 12929812 Registered 20.5.15